(untitled) (Canadian Medical Education Journal, 2013)
Introduction: The objective of this article was to analyze the theory and pedagogical basis of the use of problem-based learning (PBL) for inter-professional education (IPE) in undergraduate health science education and present evidence from a palliative care iPBL (inter-professional PBL) module that confirms the importance of the two methodologies being used together. Methods: More than 1000 student surveys collected over 4 years were analyzed for components of usefulness, enjoyment and facilitator effectiveness. A retrospective self-assessment of learning was used for both content knowledge of palliative care and knowledge of the other professions participating in the module. Results: Statistically significant gains in knowledge were recorded in both areas assessed. Medical students reported lower gains in knowledge than those in other programs. Scores were moderately high for usefulness and facilitator effectiveness. Scores for enjoyment were very high at 5.19 out of a total score of 6.0. Conclusion: There is strong theoretical and empirical evidence that PBL is a useful method to deliver IPE for palliative care education. With the evidence presented from the palliative care iPBL it is our contention that PBL inter-professional cases should be utilized more often, incorporated into IPE programs generally, and researched more rigorously.